Taste - Hurwitz, Sue, 1934- (New York : Rosen Pub. Group, 1997)
Discusses the sense of taste, including how the taste buds work.
Includes index.
0508
13 19
Keywords: Senses and sensation; Taste; Taste -- Juvenile literature